Analysis of Community Perception on Medical Mask Waste Classified as Hazardous and Toxic Waste in Surakarta, Indonesia - Andini Noviana Hartanti; Clara Estelita Damayanti; Fariz Pradana Adzil Fadzilah; Fatiya Azma Tsabita; Fauziana Erlis Safitri; Gavriel Enos Berlin; Hashfi Hawali Abdul Matin (Diponegoro University, 2023)
Hazardous and toxic waste is a substance, energy, or other component that can pollute the environment and endanger the health of living things. One example of this waste is medical waste. Medical waste is classified as hazardous and toxic waste because medical waste is infectious which has the potential to pose a risk of disease transmission. The Covid-19 pandemic has led to an increase in medical waste such as disposable masks. This mask waste requires special management so that it does not become a medium for spreading the virus. This study aims to find out how the public's understanding of mask waste is classified as infectious hazardous and toxic waste, and how the community's knowledge is in managing mask waste. The method of data collection was done through a questionnaire using a Likert approach. The data obtained were analyzed using quantitative and descriptive analysis methods. The results showed that the understanding and awareness of self-management of medical mask waste in the city of Surakarta was high, but the presentation of willingness to collect and send it was quite low. More initiatives and roles from the government and the community are needed in the management of medical mask waste.